Respostas

2013-10-21T10:43:44-02:00
 x²-x-12=0 
Δ=(-1)²-4*1*(-12)
Δ=1+48
Δ=49 x= -(-1)±√49 1±7          ,                                                                                               2*1         2 
x'= 1+7  = 4   
        2    
2
x"= 1-7 = -6/2 = -3       
          2  
 4 , -3 
2 5 2
2013-10-21T10:47:22-02:00
x^{2}-x-12=0
a=1; b=-1; c=-12
delta=1-4*1*(-12)
delta=1+48
delta=49

x= \frac{1+ou- \sqrt{49} }{2}
 x_{1} = \frac{1+7}{2}=4
 x_{2}= \frac{1-7}{2}= \frac{-6}{2}=-3
as raízes são:
S={-3;4}
espero ter ajudado!
1 5 1